Whole-body vibration exposure in unfavourable seated postures: apparent mass and seat-to-head transmissibility measurements in the fore-and-aft, lateral, and vertical directions. Issue 1 (2nd January 2023) - Amari, Maël; Perrin, Nellie
Abstract: Mobile machinery operators are exposed to whole-body vibrations (WBV) and unfavourable postures which may lead to adverse effects on the spine. 14 subjects were exposed to WBV on a rigid seat without a backrest. They adopted nine different postures. Apparent mass M A ( f ) and seat-to-head transmissibility T ( f ) were measured in the horizontal (X), lateral (Y) and vertical (Z) directions. They were compared to the reference posture from the ISO 2631-1 standard. Head and thorax inclinations in the sagittal plane had significant effects. An increase in the main resonant frequency f r, together with a decrease in | M A ( f ) | max were observed in the Z direction. A second lower frequency peak also appeared ( f r ≈ 1 H z for X, f r ≈ 2.5 H z for Z). f r increased in the X and Z directions for | T ( f ) | . | T ( f ) | max increased in the X direction. Head and thorax inclinations in the frontal and the horizontal planes had weak or non-significant effects. Practitioner summary: Mobile machinery operators are exposed to whole-body vibration and unfavourable body posture. Laboratory measurements of the apparent mass M A ( f ) and the seat-to-head transmissibility T ( f ) in the horizontal (X), lateral (Y) and vertical (Z) directions are presented for 9 postures relevant to the exposure at the driving position and to the effects of vibration on the spine.